Incorporating non-adiabatic effects in embedded atom potentials for radiation damage cascade simulations. (15th April 2015) - Mason, Daniel
Abstract In radiation damage cascade displacement spikes ions and electrons can reach very high temperatures and be out of thermal equilibrium. Correct modelling of cascades with molecular dynamics should allow for the non-adiabatic exchange of energy between ions and electrons using a consistent model for the electronic stopping, electronic temperature rise, and thermal conduction by the electrons. We present a scheme for correcting embedded atom potentials for these non-adiabatic properties at the level of the second-moment approximation, and parameterize for the bcc transition metals above the Debye temperature. We use here the Finnis–Sinclair and Derlet–Nguyen–Manh–Dudarev potentials as models for the bonding, but the corrections derived from them can be applied to any suitable empirical potential. We show with two-temperature MD simulations that computing the electronic thermal conductivity during the cascade evolution has a significant impact on the heat exchange between ions and electrons.